SIFAT MEKANIK DAN FISIK 3D-PRINTED DENTAL PHOTOPOLYMER RESINS DALAM KONDISI PEMROSESAN YANG BERBEDA - Ahmad Mamba'udin; Muhammad Akhsin Muflikhun; Adam Zuyyinal Adib; Dianisa Khoirum Sandi; Elfrida Rizky Riadini; Yuris Bahadur Wirawan (Scientific Journal of Mechanical Engineering Kinematika, 2025)
Photopolymer resins have widely applied in dentistry to fabricate temporary restorations. This work gives a complete characterization of a dental non-castable photopolymer resin prepared via Digital Light Processing (DLP) 3D printing. Specimens were printed at layer thicknesses of 0.05, 0.075, and 0.1 mm, followed by post-cured treatments under UV light for 10, 20, and 30 minutes. A series of material characterization tests were performed, including assessments of hardness, moisture absorption behavior, and density measurements. The results indicate that hardness and moisture content are significantly impacted by post-curing time, while extended curing times resulted in greater specimen’s hardness and decreased moisture content. An increase in layer thickness led to a gradual reduction in hardness. A maximum hardness value of 57.7 Shore D was observed in the 3D-printed specimen, along with a highest moisture content of 1.05% MC. As expected, the specimens exhibited consistent density (1.19 ± 0.02 g/cm³) throughout all layer thickness and curing time variations. This study highlights the critical need to understand how process parameters affect dental non-castable photopolymer resin properties prior to clinical implementation.